Forty-seven new species of Sinopoda from Asia with a considerable extension of the distribution range to the South and description of a new species group (Sparassidae: Heteropodinae) - Grall, Elena; Jäger, Peter (Zootaxa, 2020)
Up to current knowledge, the spider genus Sinopoda Jäger, 1999 is distributed in South-, East- and Southeast-Asia. New material treated in this paper include new records from Brunei, India, Indonesia, Thailand and Vietnam. Forty-seven new Sinopoda species are described: S. aenyk spec. nov. (female; Laos), S. arboricola spec. nov. (male, female; Malaysia), S. assamensis spec. nov. (female; India), S. bifurca spec. nov. (male, female; China), S. bispina spec. nov. (male; Myanmar), S. caeca spec. nov. (female; Laos), S. chiangmaiensis spec. nov. (male, female; Thailand), S. cornuta spec. nov. (male, female; Indonesia), S. deminutiva spec. nov. (male; Laos), S. emei spec. nov. (female; China), S. empat spec. nov. (male; Malaysia), S. flexura spec. nov. (female; Indochina), S. hainan spec. nov. (male; China), S. hanya spec. nov. (male; Malaysia), S. incisura spec. nov. (female; China), S. inthanon spec. nov. (male; Thailand), S. kalaw spec. nov. (female; Myanmar), S. kambaiti spec. nov. (male; Myanmar), S. kamouk spec. nov. (female; Laos), S. kieo spec. nov. (female; Laos), S. kinabalu spec. nov. (male; Malaysia), S. konglor spec. nov. (female; Laos), S. kyee spec. nov. (female; Myanmar), S. lebar spec. nov. (female; Indonesia), S. longicymbialis spec. nov. (male, female; Thailand), S. lot spec. nov. (female; Thailand), S. maculata spec. nov. (female; Malaysia), S. mat spec. nov. (female; Vietnam), S. matang spec. nov. (male, female; Malaysia), S. nanphagu spec. nov. (female; Myanmar), S. parva spec. nov. (male; Malaysia), S. phathai spec. nov. (female; Thailand), S. phiset spec. nov. (female; Thailand), S. phom spec. nov. (male, female; Thailand), S. reinholdae spec. nov. (female; Malaysia), S. rotunda spec. nov. (female; China), S. ruam spec. nov. (female; Thailand), S. silvicola spec. nov. (male, female; China), S. sulawesia spec. nov. (male, female; Indonesia), S. tawau spec. nov. (female; Malaysia), S. thieu spec. nov. (female; Vietnam), S. tibang spec. nov. (female; Indonesia), S. tilmanni spec. nov. (male, female; Malaysia), S. tralinh spec. nov. (female; Vietnam), S. tuber spec. nov. (female; Malaysia), S. unicolor spec. nov. (female; Thailand) and S. wayala spec. nov. (female; China). The female of S. exspectata Jäger & Ono, 2001 and the males of S. scurion Jäger, 2012 and S. steineri Jäger, 2012 are described for the first time. Males of S. tengchongensis Fu & Zhu, 2008 and S. triangula Liu et al., 2008 and females of S. crassa Liu et al., 2008 and S. licenti (Schenkel, 1953) are redescribed. In addition to the okinawana-group, a second species-group is diagnosed, the chiangmaiensis-group, which includes S. chiangmaiensis spec. nov., S. lot spec. nov. and S. phathai spec. nov. All three species occur in north-western Thailand. Twenty new species are described from caves, some of which have distinct cave adaptations: S. caeca spec. nov. is the second known eyeless huntsman spider, S. kamouk spec. nov. has two remnants of eyes without pigments, S. empat spec. nov. has four remnants of eyes without pigmentation and S. tralinh spec. nov. has all eight eyes but without pigments. All other new species herein described have eight functional eyes.